NEURO-LINGUISTIC PROGRAMMING (NLP) FOR INTERVENING WITH CHILDREN WHO HAVE LEARNING DIFFICULTIES - Irsyad, Sandy; Casmini, Casmini (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2023)
In the process of learning, some students may encounter difficulties. To ensure success and achievement in learning, educational institutions, particularly schools, must provide appropriate interventions. These interventions should be directly applied by the teacher. Learning is a crucial aspect of a student's academic journey. Neuro-linguistic programming (NLP) is a form of counseling that can help identify learning difficulties. The objective of this research is to: The research methodology employed was library research with an analytical method, specifically content analysis. The purpose of this research is to explore the application of neuro-linguistic programming in interventions for children with learning difficulties. The findings indicate that neuro-linguistic programming can be used by teachers to build relationships with children and help overcome learning difficulties. By implementing this approach, teachers can map students based on their representation system, which can facilitate building rapport and conducting counseling and therapy using NLP techniques. Additionally, teachers must build closeness with students, use appropriate language during teaching, and provide guidance and counseling to children with learning difficulties.